Dampak Residu Pestisida Terhadap Kepadatan Dan Keanekaragaman Jamur Tanah Pada Lahan Sayuran - Benu, Martha; Adutae, A.S.J; Mukkun, Lince (Bumi Lestari; Vol 19 No 2 (2019)DO - 10.24843/blje.2019.v19.i02.p03, 2019)
The use of pesticides in agricultural soils in addition to a positive impact because it has a phytoponic effect for plants, also cause negative impacts on the environment. Pesticide residues in agricultural soils may cause disruption to the growth and diversity of useful microorganisms in the soil such as soil fungi. Fungi play an important role in nutrient cycling, disease control, binding of soil particles and as a remodel in the soil web chain. This research was conducted in farmer's land of Noelbaki village, Kupang Tengah sub-district, Kupang regency. The purpose of this research is to know the residue content of pesticide, population density and soil fungi diversity on vegetable land applied by pesticide and without pesticide. The research method is survey and sampling of soil on vegetable land application of pesticide and without pesticide soil type Vertisol and Inceptisol. The pesticide used as reference for test of active ingredient profenofos 500 g / l, lamda-cilhalotrin 106 g / l, permethrin 20.04 g / l, carbosulfan 200,11 g / l, dimetoate 400 g / l, mankozeb 80% and propineb 70% from classes of pyrethroids, carbamates and organophosphates. Analysis of pesticide residues on soil samples of soil pesticides Vertisol and Inceptisol detected residues of Lamda-cihalotrin and Dimethoat with concentrations of 0.060 ppm and 0.042 ppm respectively. Pesticide residue in the soil is below the BMR of 0.10 ppm. Population density analysis of Vertisol and Inceptisol soil type soil samples respectively (NV-1) 71.6 cfu g-1 and (NI-1) 21.6 cfu g-1 and without pesticides respectively (NV-2) 16.6 cfu g-1 and (NI-2) 29.2 cfu g-1. The analysis of soil pesticide soil diversity of Vertisol and Inceptisol soils respectively (NV-1) 1,608 (NI-1) 1,579 and without pesticide respectively (NV-2) 1.584 and (NI-2) 1,595. Result of analysis of medium soil fungi diversity where H> 1. The types of fungi that are identified are Penicillium, Aspergillus niger, Aspergillus candidus, Aspergilus flavus, Aspergilus nidulans, Fusarium, Trichoderma, and Mucor.